Thermoresistive Properties of Graphite Films - Камінський, В.М.; Ковалюк, З.Д.; Боледзюк, В.Б.; Водоп’янов, В.М.; Іванов, В.І.; Заполовський, М.В. (Сумський державний університет, 2025)
This work investigates the thermoresistive properties of graphite films made on different types of substrates. The study of the graphite films created by different methods: freehand drawing on paper using different types of graphite (including ordinary pencils), as well as vacuum deposition on InSe and SiO2 substrates. The temperature dependence of the resistance of the graphite films in the range of 273÷380 K was measured, and the mechanisms of current flow were discussed. The experimental results demonstrate a decrease in resistance with increasing temperature for all structures of graphite films, with variations depending on the uniformity of the film surface and the types of graphite used. There are calculated the height of the barrier at the grain boundary, which plays an important role in determining the resistance of the films. It is concluded that both drawn and vacuum-deposited graphite films exhibit thermoresistive properties, and the resistance depends on the height of potential barriers in the polycrystalline structure. The experimental data are approximated within the framework of known theoretical models. The temperature coefficient of resistance is calculated. The obtained results are important for the development and calibration of thermistors in various electronic applications, offering an understanding of the resistance behaviour of graphite films under different temperature conditions.
Keywords: Graphite on paper, Thermistor, Temperature coefficient of resistance.